2021
DOI: 10.1002/tee.23477
|View full text |Cite
|
Sign up to set email alerts
|

Various Characteristics of Severely Aged Flame‐Retardant Cross‐Linked Polyolefin

Abstract: Flame-retardant cross-linked polyolefin (FR-XLPO), is widely used as insulators for electric cables. Several cables installed in nuclear power plants must be functional even when they suffer a severe accident. Therefore, sheets of FR-XLPO were exposed to heat, gamma rays, and high-temperature steam. Before and after such aging treatments, samples' mechanical and thermal properties and infrared and THz absorption spectra were measured. As a result, it has become clear that FR-XLPO is fairly resistant to superhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The MIR absorption due to carbonyl groups is a typical indicator of the oxidation of the polymeric insulation of a cable [ 4 , 9 , 10 , 11 , 15 ]. Figure 4 a shows the variation in the integrated spectral intensity due to carbonyl groups in the acid form, measured on the outer surface of each specimen among those subjected to different treatments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MIR absorption due to carbonyl groups is a typical indicator of the oxidation of the polymeric insulation of a cable [ 4 , 9 , 10 , 11 , 15 ]. Figure 4 a shows the variation in the integrated spectral intensity due to carbonyl groups in the acid form, measured on the outer surface of each specimen among those subjected to different treatments.…”
Section: Resultsmentioning
confidence: 99%
“…(EPDM) [8,9], FR cross-linked polyolefin [10,11], silicone rubber [12,13], and hard and soft epoxy resins [14][15][16] as typical polymeric insulating materials used in safety-related cables and electrical penetrations. As a result of such extensive research, we have found that oxidation and hydrolysis, as well as cross-linking and the breaking of chemical bonds, are fundamental degradation factors common to all of the polymers studied.…”
Section: Superposition Of Time-dependent Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding this, several research projects such as 'European Tools and Methodologies for an efficient ageing management of nuclear power plant Cables (Team Cables)' conducted mainly by the University of Bologna [1, 2], 'Light Water Reactor Sustainability (LWRS) Programme' organised by the US Department of Energy [3,4], and a Japanese one entrusted by the Secretariat of the Nuclear Regulation Authority in Japan are recently actively involved in the degradation of insulating polymers for use in NPPs. For conducting the last project, we have been doing many pieces of research on the degradation of various insulating polymers used in safety-related cables, such as cross-linked polyethylene (XLPE) [5,6], flame-retardant (FR) XLPE [7], FR ethylene-propylene-diene rubber [8,9], FR cross-linked polyolefin [10,11], and silicone rubber [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Much research has also been carried out in Japan to examine the degradation behavior of various insulating polymers such as silicone rubber (SiR), soft epoxy resin (SE), flame-retardant ethylene-propylene-diene rubber (FR-EPDM), flame-retardant cross-linked polyolefin (FR-XLPO), non-flame-retardant cross-linked polyethylene (NFR-XLPE), and flame-retardant cross-linked polyethylene (FR-XLPE) in a project entrusted by the Nuclear Regulation Authority in Japan [6][7][8][9][10][11][12][13][14][15][16][17]. Here, NFR-XLPE and FR-XLPE are used in both pressurized-water type and boiling-water type NPPs, in Japan, depending on the purpose of each cable.…”
Section: Introductionmentioning
confidence: 99%